Reflexões sobre uma experiência com a produção de textos on-line: uma análise das emoções expressas por alunos de ensino fundamental - Silva, Leandro Coimbra da (Universidade do Vale do Rio dos Sinos, 2016)
This work aims to identify how students from a 6th grade class at a public school in Novo Hamburgo, Brazil, linguistically express the perception of their first text production experience from Moodle. Thus, I tried to reflect on the implications of this perception to the process of teaching and learning aiming at the digital literacy. In this setting, then, we proposed five classes in a Moodle institutional group from June to July, 2014. The classes were driven from the Brazilian Olympiad of Portuguese Language program, and the daily postings of the virtual environment constitute our research corpus. Having that, I sought to build pathways to understand the triad on-line teaching/cyberculture/digital literacy through a theoretical background which considers the Appraisal Theory (MARTIN; WHITE, 2005) aided by the approach of Cognitive Psychology (SCHERER, 2005), at the intersection between digital literacy (SOARES, 2002; COSCARELLI, 2014) and multiliteracies (ROJO, 2009; 2012), and the issues relating to cyberculture/cyberspace (LÉVY, 1999; LEMOS, 2000-2008). The analysis methodology is supported on the conceptual categories of the Appraisal Theory and on the guiding questions brought by the triad at Rojo (2009), Soares (2002, 2003, 2010), Coscarelli and Santos (2007), Coscarelli (2014) Franciosi, Medeiros and Cola (2003), Tori (2009), Lemos (2000), Lévy (1999), Dias (1999), Freitas (2010) and Santaella (2013). In this process, data is organized from the Appraisal Groups (AGs) design (WHITELAW, GARG; ARGAMON, 2005), which are coherent groups of words that together express a particular attitude. The results show the occurrence of 183 adjectives distributed in 163 AGs, from which we extract to reflect the categories of analysis (1) class, (2) Moodle, (3) production, (4) experience and (5) evaluator. Our analysis shows that the Appraisal Theory is an effective method both to evaluate the digital environment, consolidating its position as a teaching-learning place in primary education, and for the emotion lexical mapping of the age group that constitutes the analyzed group. Moreover, it shows the possibility of a satisfaction setting of an elementary school student to the process of digital literacy from the virtual learning environment.
Keywords: Letramento digital; Sistema da avaliatividade; Análise de sentimentos; Blended learning; Cibercultura; Digital literacy; Appraisal theory; Sentiment analysis; Blended learning; Cyberculture; ACCNPQ::Lingüística, Letras e Artes::Lingüística